Leptospira seroprevalence in sewer workers and rats and environmental presence in selected cities of Metro Manila, Philippines - Jamora, Renard M. (Manila, 2018)
Leptospirosis is a major public health issue in many countries, especially in South-East Asia including the Philippines. Outbreaks are prominent in the airy season of the (June to November) and just after these months in flood-susceptible areas. Leptospirosis is an occupational risk both in rural and urban settings. Vulnerable groups iclude farmers, abattoir workers, veterinarians and sewer workers amonth others. Rodents, especially rats, are the most important reservoir of the disease and can constinuously shed leptospira through their urne and contaminate the environment, including the work environment of sewer workers. Serum samples obtained from 105 sewer workers and 40 cptured rats in the west zone of Metro Manila were subjected to microscopic agglutination test (MAT). Sera that turned out positive in screening MAT were further subjected to quantitative MAT with a cut-off titer of 1:100 (ie., used mainly to detect for exposure of sewer workers to Leptospira) in humans and 1:20 in rats. Rat kidneys of 40 captured rats and 50 environmental samples were subjected to culture. Culture-positive samples were subjected to rrl-and flaB-PCR. Pathogenic Lepstospira isolates were serotyped using polyclonal antibodies raised against seven different serovars of Leptospira. In addition, flaB-PCR positive environmental isolates were further analyzed through 16S rRNA gene sequence determination. Based on thr results, 4.8% (5/105) of the sewer workers were seropositive for Leptospira-agglutinating antibodies, reacting to servar Mini alone. All seropositive sewer workers were found to wade in combined sewer overflow (CSO), manholes and septic tanks as a part of their jobs. Data gathered also showed that three of them get sewer water splashes in their eyes, nose or mouth while cleaning at least once or twice a week and all of them go to work despite having cuts or bruises. Therefore, it was highly likely that the presence of Leptospira-agglutinating antibodies among the five sewer workers can be attributed to the constant exposure to rat urine-contaminated sewer environment. On the other hand, the overall Leptospira-seroposivity among the captured rats was 72.5% (29/40). Based on MAT, antibodies against serovar Manilae (37.9%) was the most frequently detected, followed by servars Losbanos (17.2%), Pomona (10.3%), Hebdomadis (10.3%), Javanica (10.3%) and Mini (6.9%). Multiple serovars were also detected in 6.9% (2/29) of the seropositive samples. Moreover, leptospires were detected via culture in 12.5% (5/40) of the rat kidney samples. All five isolates were found to be pathogenic using flaB-PCR. Each of the five pathogenic isolates reacted to polyclonal antibodies from rabbits raised against different Leptospira serovars. Four of the five isolates (ie., RMJR1, RMJR2, RMJR3 and RMJR4) reacted to serovar Losbanos while one isolate recated to serovar Icterohaemorrhagiae (RMJR5). Three of the rat kidney isolates came from rats in Muntinlupa (ie., RMJR2, RMJR3 and RMJR4), RMJR1 came from a rat in Navotas and RMJR5 came from a captured rat in Paranaque. Fifty percent (25/50) of the environmental samples (ie., 16 soil and 9 wastewater) were culture and rrl-PCR positive, hence belonging to the genus Leptospira. Among the Leptospira-positive cultures, two isolates from soiul and none from wastewater samples were found positive in flaB-PCR. The flaB-PCR positive soil samples were isolated from Navotas City (RMJS2) and in the Municipality of Muntinlupa (RMJS16). Based on the ?. -
Thesis (Doctor of Public Health-Medical Microbiology)--University of the Philippines Manila, May 2018.
Not available to general public.
Keywords: Leptospira; Leptospirosis; Rats as carriers of disease